Patient-Level Costing in the Hospitals of Southern Region of Saudi Arabia - Mehmood, Asim (Universiti Malaysia Sarawak, 2022)
Health Systems aims to deliver high-quality care through efficient and effective services. Fund allocators require reliable healthcare cost information from hospitals for efficient budgeting and resource allocation. This study aimed to: (i) develop a DRG-based Casemix System and (ii) estimate cost per inpatient admission. A retrospective cross-sectional descriptive study was conducted at two hospitals in Jazan Region, Saudi Arabia namely, King Fahd Central Hospital (KFCH), the only tertiary hospital in the Region and Abu Aresh General Hospital (AAGH), a secondary care hospital using 12,979 and 8,452 hospital discharges in 2018 respectively. This study was conducted in two parts with Part 1: Developing and assigning of DRG codes to each inpatient, and Part 2: Resource consumption costing estimation using the step-down approach. At KFCH, 38% of the cases had surgical procedures and 62% of the cases were treated in different medical specialties, while at AAGH 23.20% had surgical procedures and 76.80% of the cases were treated in different medical specialties. The majority of the procedures conducted at both hospitals were from CMG "O" (Deliveries) 19.08% and 26.52% respectively. The highest number of inpatient medical cases at KFCH were from CMG "B" (Hepatobiliary & Pancreatic System), with 22.21% while at AAGH the highest number of inpatient medical cases were from CMG "O" (Deliveries) with 31.03%. At both hospitals, most patients were in severity Level “I” (only 1 diagnosis/procedure) with 96.56% and 93.70% respectively. A total of 269 DRGs of various severity levels were assigned to patients at KFCH of which 12.04% were from DRG “B-4-13-I” (Other Liver Diseases-Mild), while at AAGH 290 DRGs were assigned to patients with 23.15% were from DRG code "O-6-13- I" (Vaginal Delivery– Mild). The highest operational cost at KFCH at 24.37% was at the medical ward, while at AAGH, the highest operational cost was at surgical ward with 39.36%. At KFCH, the highest cost per patient per day was for the cardiac surgery ward (SAR16,219), while at AAGH the highest cost per patient per day was for Plastic Surgery/Burns ward (SAR11,814). The highest average cost per DRG at KFCH was for the DRG group "I-4-10-I" (Acute Myocardial Infarction–Mild, SAR72,987), while at AAGH, the highest average cost was for the DRG group " L-1-50-I " (Breast Operations-Minor, SAR101,336). This was the first hospital costing study ever conducted in the Region and its findings provides important information on health care cost at tertiary and secondary hospital settings. This information can be adopted as a primary tool and reference for further studies in other regions of Saudi Arabia. Keywords: Patient-Level Costing, Casemix, costing, Diagnosis Related Groups, hospital, Saudi Arabia